Positive Feedback From Male Authority Figures Boosts Women's Math Outcomes. (March 2018) - Park, Lora E.; Kondrak, Cheryl L.; Ward, Deborah E.; Streamer, Lindsey
People often search for cues in the environment to determine whether or not they will be judged or treated negatively based on their social identities. Accordingly, feedback from gatekeepers—members of majority groups who hold authority and power in a field—may be an especially important cue for those at risk of experiencing social identity threat, such as women in math settings. Across a series of studies, women who received positive ("Good job!") versus objective (score only) feedback from a male (vs. female) authority figure in math reported greater confidence; belonging; self-efficacy; more favorable Science, Technology, Engineering, and Mathematics (STEM) attitudes/identification/interest; and greater implicit identification with math. Men were affected only by the type of math feedback they received, not by the source of feedback. A meta-analysis across studies confirmed results. Together, these findings suggest that positive feedback from gatekeepers is an important situational cue that can improve the outcomes of negatively stereotyped groups.